Use of virtual reality in the reduction of pain after the administration of vaccines among children in primary care centers in Central Catalonia: Randomized clinical trial - Mercedes De La Cruz Herrera; Aïna Fuster-Casanovas; Queralt Miró Catalina; Mireia Cigarrrán Mensa; Isabel Vilanova Guitart; Antonio Agüera Sedeño; Josep Vidal-Alaball; Sergi Grau Carrión (PLoS ONE, 2025)
Background Pain and anxiety caused by vaccination and other medical procedures in childhood can generate discomfort in both the patient and their parents. Virtual reality is a non-pharmacological distraction technique, capable of diverting patients’ attention to a virtual environment, potentially reducing pain signals during the procedure and becoming a method of analgesia, reinforcing traditional methods. The main objective of this study was to evaluate the reduction of pain and anxiety following the administration of two vaccines. Patients and methods A randomized, multicenter, open, parallel and controlled clinical trial was carried out in two assigned groups; in which were included 300 children aged 3 and 6 years, who were candidates to receive two vaccines. The intervention group used virtual reality glasses while the control group received traditional care. Pain and anxiety were assessed using validated scales; the heart rate and the satisfaction of legal guardians were also recorded. Results A total of 150 patients were included in each group. 53.3% of the intervention group reported no pain during the first vaccination, compared to 25.3% of the control group; with regard to the second vaccination, 49.3% of the virtual reality group reported no pain, compared to 21.3% of the control group. 71.1% of the intervention group faced the first vaccination calmly; 52% and 56.7% did not show anxiety at the end of the vaccination respectively; as for the control group, 71.8% faced the first vaccination calmly, 23.3% did not show anxiety at the end of the first intervention and 19.3% did not show anxiety at the end of the second vaccination. The heart rate was significantly lower in the intervention group. The satisfaction of legal guardians in the virtual reality group was higher than in the control group. Conclusions the use of virtual reality reduces pain and anxiety during vaccination in pediatric population. Registered in ClinicalTrials.gov: NCT06313762.